Association between Dietary Habits and Sperm Quality: Evidence from a Multicenter Fertility Study in Malaysia - Muhamad, Suriyani; Majid, Nur Fatma Hasni; Zakaria, Noor Salihah (Malaysian Journal of Medical Sciences, 2026)
Background: A range of factors, sociodemographic and lifestyle-related, are instrumental in shaping male fertility, including dietary practices. However, limited studies have examined these associations in the Malaysian context. This study investigates the connections between dietary habits and sperm quality among male patients attending fertility clinics. Methods: A cross-sectional design was used to examine male patients attending four fertility clinics in Peninsular Malaysia. Sociodemographic data, dietary habits, and sperm quality classifications (normal vs abnormal) were collected. Assessment of dietary consumption involved the use of validated food frequency questionnaires, while data on sperm quality were retrieved from patient’s medical records. Analysis of binary logistic regression was executed to assess food group consumption’s association with sperm quality, while controlling for household income and education level. Results: Sperm quality was significantly associated with education level (P = 0.001) and household income (P = 0.017), but not with age or body mass index (BMI). Higher fruit consumption was significantly associated with better sperm quality (aOR = 0.83; 95% CI: 0.73, 0.94; P = 0.004), while frequent fast-food intake was linked to poorer sperm quality (aOR = 1.55; 95% CI: 1.02, 2.35; P = 0.039). Vegetable, dairy, meat, caffeine, and sugar-sweetened beverage consumptions were not significantly associated with sperm quality. Conclusion: This study demonstrates the associations between dietary practices, socioeconomic variables, and male fertility. Higher fruit intake and socioeconomic status were associated with better sperm quality, whereas fast-food consumption was linked to poorer outcomes. The study reinforces the significance of diet and socioeconomic status in shaping male reproductive well-being.